The The Influence of Life Stressors on Mental Health Disorders in Adolescents - Bachtiar, Nanda; Latifah, Ulfatul (GLOBAL HEALTH SCIENCE GROUP, 2024)
Based on the 2018 mental health data for adolescents in Indonesia, it was found that 9.8% experienced emotional mental disorders with symptoms of depression and anxiety among those aged >15 years. Adolescent mental health significantly influences their individual futures and has broader implications for families and communities. Emotional issues in adolescents can serve as life stressors, which, in turn, become a risk factor affecting their mental health. This research aims to investigate the influence of life stressors on the mental health of adolescents. This study adopts a quantitative approach with an observational design. The population comprises adolescents in Tegal City, and data collection employs the Cluster Random Sampling technique. The sample size, determined using the Slovin formula with a 0.05 error level, is set at 510 individuals. Data are collected through a questionnaire distributed via Google Forms. The data analysis utilizes multiple linear regression analysis.The research findings indicate a significant influence of life stressors on Mental Health Disorders. It can be inferred that life stressors play a substantial role in mental health disorders among adolescents, highlighting them as risk factors for mental health issues in this demographic. The involvement of parents, teachers, community leaders, and the surrounding society is crucial in providing guidance and positive role models for adolescents.This study sheds light on the urgency of collective efforts in addressing life stressors and promoting mental well-being among adolescents, emphasizing the pivotal roles of key stakeholders in the community